THE EFFECTIVENESS OF USING POP UP BTHE EFFECTIVENESS OF USING POP UP BOOK MEDIA ON LANGUAGE ABILITY IN EARLY CHILDRENOOK MEDIA ON LANGUAGE ABILITY IN EARLY CHILDREN - Rahimah Rahimah (Proceeding International Seminar of Islamic Studies, 2023)
This research was conducted at RA Al-Is Syah Hakim Medan. This type of research is qualitative research. This research method uses qualitative research. The population is 29 children with total sampling technique, so that the entire population is used as a sample. This study aims to determine: (1) linguistic verbal intelligence of children; (2) Linguistic verbal intelligence of children using pop up book media; (3) The significant influence of pop up book media on the linguistic verbal intelligence of children at RA Al-Isyah Hakim Medan. The results of the study show that the use of pop up book media affects the linguistic intelligence of children aged 5-6 years. This is illustrated by the visible results of the research so that it can be stated that there is a significant effect of the use of pop-up book media on the verbal-linguistic intelligence of children aged 5-6 years at RA Al-Isyah Hakim Medan. Media Pop Up Book, Linguistic Intelligence.